PENGARUH KAPASITAS SUMBER DAYA MANUSIA, IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA), SISTEM AKUNTANSI KEUANGAN DAERAH (SAKD) TERHADAP KUALITAS LAPORAN KEUANGAN PADA OPD KABUPATEN GIANYAR - Ni Kadek Sri Dewi Asih; Ni Putu Trisna Windika Pratiwi (Hita Akuntansi dan Keuangan, 2021)
his research aims to test the influence of human resource capacity, implementation of regional management information system, regional financial accounting system on the quality of financial statements in OPD Gianyar Regency. The method used in this study is quantitative method with primary data through questionnaire and measured by likert scale. The sampling method in this study used purposive sampling. In this study, the sample used was 94 respondents consisting of sub-section heads, treasurers and accountants from 39 OPD Gianyar Regency. The data analysis technique used is multiple linear regression test. The results of this study show that human resource capacity has no significant effect on the quality of financial statements, while the implementation of regional management information systems and regional financial accounting systems have a positive and significant effect on the quality of financial statements.